Development and Validation of PowerPoint-Based Interactive Game Media for Science Learning in Islamic Elementary Schools - Benny Angga Permadi; Md. Fajlay Rabbi; Rojana Zahro Wajihan; Hayatun Najah; Nabil Gustian (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2026)
The rapid development of technology and information has inevitably influenced the field of education. This development presents significant challenges for teachers and educational practitioners, who must develop innovative approaches to effectively integrate technology into the teaching and learning process. This development research aims to determine the specifications, validity, teacher and student responses, and effectiveness of an interactive learning media based on a PowerPoint game on the topic of characteristics of living things for third-grade students at MI Miftahul Ulum Gondang. The research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, validation sheets, and questionnaires. The data analysis techniques included validation sheet analysis, questionnaire analysis, descriptive statistical analysis, normality testing, paired-samples t-tests, and N-gain analysis to assess the effectiveness of the developed media. Based on the validation results, the material expert evaluation reached 85%, the media expert evaluation reached 90%, and the language expert evaluation reached 88.8%. These results indicate that the interactive PowerPoint-based game is valid and feasible for instructional use. Furthermore, student responses showed a very positive result at 90.9%, while teacher responses reached 97.5%, indicating strong acceptance and usability of the media in classroom learning. Quantitative data analysis revealed an average effectiveness score of 59.27%, demonstrating a meaningful improvement in students’ understanding after using the developed media.